Use of buccal myomucosal flap for palatal lengthening in cleft palate patient: Experience of 20 cases - Don Varghese; Shubharanjan Datta; Annie Varghese (Contemporary Clinical Dentistry, 2015)
Background: The purpose of this review was to assess the effectiveness of the buccal myomucosal flap in secondary repairs of cleft palate in 20 patients. Patients and Methods: Totally, 20 patients, who underwent secondary palatoplasty between 5 years and 8 years in which a buccal myomucosal flap was used, were reviewed retrospectively. All patients had undergone at least one previous attempted repair at other institutions. Indications for the secondary repair included velopharyngeal incompetence and/or oronasal fistula. Patients were evaluated preoperatively for oronasal fistula status, velopharyngeal competence, nasal resonance, speech quality, and nasal escape. Results: The buccal myomucosal flap was used in all 20 patients, and there was marked increase in the quality of speech as well as nasal regurgitation decreased. In patients with levator dysfunction due to poor primary surgery and glottal speech the results were inconclusive Conclusion: Palate re-repair combined with a buccal myomucosal flap, occasionally in conjunction with other techniques, is an effective method for correcting failed cleft palate repairs. Minimum donor site morbidity and complication makes the buccal flap a useful armamentarium of a cleft surgeon.